If it's not what You are looking for type in the equation solver your own equation and let us solve it.
0.3(2x-3)=0.75(2-4x)
We simplify the equation to the form, which is simple to understand
0.3(2x-3)=0.75(2-4x)
Reorder the terms in parentheses
+( + 0.6x-0.9)=0.75*(2-4x)
Remove unnecessary parentheses
+ 0.6x-0.9=0.75+*(+2-4x+)
Reorder the terms in parentheses
+ 0.6x-0.9=+(+1.5-3x)
Remove unnecessary parentheses
+ 0.6x-0.9=+1.5-3x
We move all terms containing x to the left and all other terms to the right.
+ 0.6x+3x=+1.5 + 0.9
We simplify left and right side of the equation.
+3.6x=+2.4
We divide both sides of the equation by 3.6 to get x.
x=0.66666666666667
| 23x-7x+4x=0 | | p(5)=7x-3 | | 8-5x+6x=10 | | 2(5x-4)=6x+2 | | .85+.8-x=2.4 | | 1.99b=68.88 | | 7(8k+1)+4k= | | 8+7(5-3c)+4c= | | x^2+15x-16= | | 72+7d=15 | | -8b+7-2=-19 | | 4+2.50b=21.50 | | 7x-16=8x+2 | | p^2-7p+12= | | 9w^3-12w^2=0 | | -3x+4x-5x=0 | | 4(m-6)+2=4m-12 | | 2(5x-4)=5x+5 | | x/4+2x/8=4 | | 2(5x-4)=3x+5 | | (6x-17)+(4x-12)+(2x+15)=180 | | 20*2+14=9*n | | 7x(7.5+z)= | | 3x^2-55x-58=0 | | z+(-2z+10)=-z+2(2z-3) | | 2(5x-4)=3x+2 | | W^2-8w-42=0 | | -9(6+u)-2v=-10 | | 2(x-5)-3(x+1)=0 | | (14-3)X(5-2)2= | | 21x+23= | | 8x+1=1+2.4x |